2008
DOI: 10.1186/1471-2474-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of lumbar spine instability between laminectomy and bilateral laminotomy for spinal stenosis syndrome – an experimental study in porcine model

Abstract: Background: The association of lumbar spine instability between laminectomy and laminotomy has been clinically studied, but the corresponding in vitro biomechanical studies have not been reported. We investigated the hypothesis that the integrity of the posterior complex (spinous process-interspinous ligament-spinous process) plays an important role on the postoperative spinal stability in decompressive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 29 publications
3
85
0
2
Order By: Relevance
“…We suggest that this may help prevent spinal instability, which can occur after traditional laminectomy [9]. Indeed, Tai et al [17] have suggested that maintained integrity of the posterior complex helps stabilize the decompressed spine. In addition to preserving the facet joint and supraspinal ligament, PLF or PLIF with or without instrumentation was performed for patients with degenerative spondylolisthesis, adult lumbar scoliosis, or multilevel stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that this may help prevent spinal instability, which can occur after traditional laminectomy [9]. Indeed, Tai et al [17] have suggested that maintained integrity of the posterior complex helps stabilize the decompressed spine. In addition to preserving the facet joint and supraspinal ligament, PLF or PLIF with or without instrumentation was performed for patients with degenerative spondylolisthesis, adult lumbar scoliosis, or multilevel stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Laminectomy is the standard option for surgical decompression of spinal stenosis. However, traditional laminectomy involves extensive removal of the posterior elements including the lamina, spinous processes, superspinous ligaments, interspinous ligaments, and even facet joints, which may result in iatrogenic spinal instability [16,17]. Foraminotomy has become increasingly popular for treatment of patients with lumbar stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…[3,6,8,9,12,16,17] Although recent biomechanical studies have shown that a number of spinal devices can be used for rigid fixation and fusion at the treated level, little attention has been focused on the adjacent segment instability. [2,5,6,8,12,13,[16][17][18] The present study focused on the adjacent segment instability. As adjacent segment mobility increased, the anterior and posterior structures maintained stability and prevented instability.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The posterior structures of the facet joints are particularly important stabilizers of the motion segment. The orientation of the facets in the lumbar spine facilitates flexion and extension and aids in resisting torsion and shear load.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation